The Influence of the Quantum Learning Teaching Model on Learning Outcomes Moderated by Learning Motivation (Experimental Study at SMAN 1 Lohbener) - Via Nurafifah; Mahfud Muziburrohman; Poy Saefullah Zavender; Widayati (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
The Quantum Learning Learning Model is a learning model that emphasizes the involvement of all aspects, interaction between teachers and students, thus creating a pleasant learning environment. The learning outcomes in class X at SMAN I Lohbener are quite good, but there are some students who still get low learning outcomes. Motivation to learn is al quite good, it's just that every child definitely has a different learning style, this is one of the things that fosters motiva to learn. The aim of this research is to analyze whether there are differences in learning outcomes and learning motivation between classes that we the quantum learning learning model (experimental class) and those that use the discovery learning method (control class). And to analyze whether learning motivation can strengthen or weaken learning outcomes. To find out learning outcomes, they will be tested with objective tests and to find out student motivation to learn, they will be given a questionnaire, and will be supported by documentation to find out the situatic SMAN 1 Lohbener). The results of the research show that there is a sificant difference in the learning outcomes in class And for learning motivation, there is also a significant difference between the posttest lear outcomes between the experimental class and the cool class, namely with a significant value of 0.000. Meanwhile, the Sobel test got a score of 0.716, which indicates that motivation does not moderate learning outcomes.